The New York Yankees and the conservative use of space - Bates, Benjamin (Ethnologies, 2002)
Abstract New York City’s “Canyon of Heroes”, the stretch of Broadway between Wall Street and City Hall, is often used as a space for celebrating sports, military, or political achievements through a parade. This essay offers an analysis of one iteration of a parade — the New York Yankees 1998 victory parade — and its (re)presentation by NBC. Drawing on Michel de Certeau’s concept of la perruque, the essay argues that a negotiation of multiple readings of this space (macro, micro, and in-between views) allow us to understand how several threads of symbols are woven together to create a politically and economically conservative fabric of spatial representation. The essay offers implications of the conservative use of space for the theorization of spatial theory and critical intervention.